“ANALYSIS OF READING STRATEGIES IN THE PROCESS OF ENGLISH LANGUAGE LEARNING AT PRIMER AÑO DE BACHILLERATO PARALELO A STUDENTS OF UNIDAD EDUCATIVA “TOMÁS OLEAS”, PARROQUIA CAJABAMBA, DURING THE FIRST QUIMESTER, SCHOOL PERIODO 2017-2018”. - Buñay Duchi, Edgar David (2019)
In English, reading and comprehension is one of the skills that most frequently present problems, stemming from the lack of adequate strategies on the part of the teacher, which greatly limits the knowledge and use of vocabulary and grammatical structures, and without this base, advancement is limited. That is why this research focuses on determining what are the main problems in reading development by students of the Unidad Educativa "Tomas Oleas" of the school year 2017-2018, which was identified as having a low reading level in the English language. The purpose of this study is to analyze how reading strategies are applied in the English language learning process, identify and select strategies, and describe how students achieve a critical thinking base. This project was developed in the Unidad Educativa "Tomas Oleas" with the participation of 34 students of the first year of baccalaureate, class "A". The study belongs to the qualitative approach with a level of exploration as the researcher seeks to identify the different teaching strategies used by the teacher and the use of ethnography due to the systematic analysis of the learning process at the research site. To achieve this objective, qualitative questionnaires and the observation technique were applied to the teacher and the students. The instrument used was an ethnographic observation sheet which was applied in the aforementioned population allowing to see the problem directly. The main results showed that the lack of use of adequate reading strategies limits the development of critical thinking in students when answering questions about the readings assigned by their teacher. The main conclusion established is that reading strategies such as texts with illustrations, translating words, dynamic questions, highlighting the main ideas are excellent for perfecting the English language but the way they are applied is not adequate. Therefore, the correct use of these strategies will promote learning goals that are achievable. Key words: Strategies, reading, learning, process.